Peran Karyawan Multinasional dalam Meningkatkan Kualitas Pelayanan di Breezbay Hotel - Dwi Anggraini; Henry Yuliamir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to describe and analyze the role of multinational employees in improving service quality at Breezbay Hotel. The issue is focused on how the contributions of multinational employees are implemented in service practices, the dynamics of cross-cultural interactions in the workplace, and their implications for guest experience. To address this issue, the study draws on theories of service quality, workforce diversity, and cross-cultural human resource management. Data were collected through in-depth interviews, non-participant observation, and documentation involving management, supervisors, local employees, multinational employees, and hotel guests, and were analyzed qualitatively using a case study approach. The findings indicate that multinational employees play an important role in enhancing service quality, particularly in terms of cross-cultural communication, empathy, and service assurance, especially when serving international guests. Although challenges such as differences in communication styles and potential miscommunication were identified, effective leadership, the implementation of standard operating procedures, and open internal communication were found to minimize these obstacles. This study concludes that multinational workforce diversity is a strategic asset that, when managed adaptively and inclusively, can improve service quality, enrich guest experience, and strengthen hotel competitiveness in the global hospitality industry.